Optimal time point for evaluation in a chronic peripheral nerve injury rat model: a preclinical study - Widodo, Wahyu; Dilogo, Ismail Hadisoebroto; Kamal, Achmad Fauzi; Antarianto, Radiana Dhewayani; Wuyung, Puspita Eka; Siregar, Nurjati Chairani; Octaviana, Fitri; Kekalih, Aria; Suroto, Heri; Aprilya, Dina; Canintika, Anissa Feby (Medical Journal of Indonesia, 2026)
BACKGROUND Peripheral nerve injury (PNI) can cause severe functional disabilities and progresses dynamically over time. Since evaluations held at different time points will yield different results, finding an optimal model for PNI comparison is needed. This study aimed to create an animal model of chronic denervation that simulates the progress of nerve injury. METHODS 6 male Sprague-Dawley rats underwent complete sciatic nerve transection in their right hind limbs, with severed nerve ends secured to a nearby muscle to prevent nerve regrowth. The rats were sacrificed at 2, 3, and 4 weeks. The assessment included walking analysis (pre- and post-injury), wet muscle weight measurement, and histological examination. RESULTS Progressive gastrocnemius muscle degeneration was observed at 3 different time points. Minimal degenerative changes were noted at 2 weeks, while extensive fibrosis (83.25 [12.19]% collagen area) appeared in the 4th week. The 3rd-week samples showed lymphocyte infiltrations, muscular atrophy, and progressive fibrosis, making it the best model for chronic PNI. CONCLUSIONS A 3-week chronic denervation model is proposed as a long-term PNI for further regenerative research.